2020
DOI: 10.1042/cs20190488
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism of mechanotransduction in vascular homeostasis and disease

Abstract: Blood vessels are constantly exposed to mechanical stimuli such as shear stress due to flow and pulsatile stretch. The extracellular matrix maintains the structural integrity of the vessel wall and coordinates with a dynamic mechanical environment to provide cues to initiate intracellular signaling pathway(s), thereby changing cellular behaviors and functions. However, the precise role of matrix–cell interactions involved in mechanotransduction during vascular homeostasis and disease development remains to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 176 publications
1
61
0
Order By: Relevance
“…However, a loss of VSMC-elastic fibers connections does not appear to be sufficient to cause aneurysmal disease, given that elastin deficiency associates with obstructive arterial diseases and VSMC over-proliferation, but not aneurysm [85,293]. TAA-causing mutation may result in the abnormal assembly, maturation, and function of focal adhesions and actively perturb focal adhesion-and force-dependent signaling in a manner that is not recapitulated by simple loss of attachments to elastin fibers [28,87,91,355]. Then, dysfunctional signaling downstream of focal adhesions would promote the upregulation of metalloproteinases and other matrix proteins, such as thrombospondin-1, which positively regulate AT 1 R and TGF-β signaling, further exacerbating ECM pathogenic remodeling [239,244,261,354].…”
Section: Proposed Model Of Taa Pathogenesis Based On the Function Of Known Causal Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a loss of VSMC-elastic fibers connections does not appear to be sufficient to cause aneurysmal disease, given that elastin deficiency associates with obstructive arterial diseases and VSMC over-proliferation, but not aneurysm [85,293]. TAA-causing mutation may result in the abnormal assembly, maturation, and function of focal adhesions and actively perturb focal adhesion-and force-dependent signaling in a manner that is not recapitulated by simple loss of attachments to elastin fibers [28,87,91,355]. Then, dysfunctional signaling downstream of focal adhesions would promote the upregulation of metalloproteinases and other matrix proteins, such as thrombospondin-1, which positively regulate AT 1 R and TGF-β signaling, further exacerbating ECM pathogenic remodeling [239,244,261,354].…”
Section: Proposed Model Of Taa Pathogenesis Based On the Function Of Known Causal Variantsmentioning
confidence: 99%
“…Loss of elastin and the increased deposition and crosslinking of collagen during aneurysm development translate into biomechanical changes that include reduced distensibility and increased stiffness of the aorta [71]. Changes in stiffness modulate VSMCs phenotypes through integrins and focal adhesions; although stiffness is generally associated with the retention of a "contractile" phenotype, excess stiffness can also increase sensitivity to growth factors, such as PDGF, which promotes a "synthetic" phenotype, and enhanced ECM stiffness has been shown to promote a switch from a "contractile" to a "synthetic" phenotype through the downregulation of DNA methyltransferase 1 [355,[371][372][373].…”
Section: Adaptive and Maladaptive Roles Of "Aortic Stiffness"mentioning
confidence: 99%
“…We hypothesize that the increased invasive capabilities of CRC tumor cells in the presence of peristalsis may be mediated by endothelial-tumor cross talk. The mechanobiology of endothelial cells has been well studied, with several reports describing how endothelial cells change cell orientation, proliferation, and cell surface markers in response to cyclic strain ( Thodeti et al., 2009 , Yamashiro and Yanagisawa, 2020 ), however the role of mechanotransduction in CRC requires further study. A non-small-cell lung cancer (NSCLC) organ chip model demonstrated that rhythmic mechanical forces mimicking breathing decreased NSCLC cell invasive behavior ( Hassell et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The human body is overly sensitive to mechanical impetus [ 1 , 2 , 3 , 4 , 5 , 6 ]. Extensive research has shown that mechanical forces play an essential role in the growth, development, repair, and remodeling of organs and their component tissues by regulating cellular and molecular pathways [ 5 , 7 , 8 , 9 , 10 ]. The mechanotransductive forces cause stresses and strains in the extracellular matrix, resulting in confirmation changes at cellular and molecular levels.…”
Section: Introductionmentioning
confidence: 99%